Penduduk Migran Dan Program Bangga Kencana Di Kabupaten Kulon Progo - Sumini Sumini; Agus Joko Pitoyo; Riza Fatma Arifa (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
The Family Development, Population and Family Planning Program (Bangga Kencana) has an important meaning in population development that must be understood by the population. Socialization and education have been carried out, but is the Bangga Kencana Program well known for the migrant population? This study explores the knowledge and participation of migrants in the Bangga Kencana Program in Kulon Progo District. Secondary data from the population development survey were analyzed using descriptive statistics, this study found, (1) migrant knowledge of good family planning, 75 percent of married migrant women aged over 20 years, (2) birth preferences in accordance with program policies, 75 percent of migrant women want to have 2 children, (3) and involvement in family resilience activity programs is still low, less than 50 percent of families join tribina activity groups. Based on this, local governments need to strengthen the strategy and promotion of the Bangga Kencana Program, especially in the family resilience program.